BORROWING WORDS IN UZBEK AND ENGLISH: A CONTRASTIVE STUDY - Abdusadikova Dilfuza Abduvayit qizi; Radjabov Nasir Nasimovich (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This article explores the process by which foreign words penetrate and become established within the lexical systems of Uzbek and English, tracing the degree to which such words are structurally assimilated and identifying the conditions that determine whether a borrowed item achieves full integration or remains marked as external. Rather than cataloguing loanwords by origin, the study focuses on the dynamic relationship between external linguistic pressure and the internal structural resistance of each receiving language. The article argues that the degree and character of lexical assimilation is shaped not only by phonological and morphological compatibility but equally by the social prestige attached to the donor language, the institutional context of contact, and the communicative domains in which borrowed words first circulate. Findings from both languages reveal that the boundary between native and borrowed vocabulary is far less stable than traditional lexicological classifications suggest.